2012
DOI: 10.1002/bjs.8867
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind crossover study of alternative stimulator settings in sacral nerve stimulation for faecal incontinence

Abstract: Patients experiencing loss of efficacy can experience improvement if alternative pacemaker settings are tested. High-frequency stimulation (31 Hz/210 µs) was preferred by more than half of the patients, and improved treatment outcome was sustained at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 34 publications
1
61
1
Order By: Relevance
“…In contrast, changing frequency and pulse width has not been routine. Although two studies have demonstrated that changes in stimulation frequency (to higher frequency) and reductions in pulse width can have a short‐term positive impact on SNM outcome, to the present authors' knowledge no study has systematically explored a range of frequencies to determine whether an optimum exists.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, changing frequency and pulse width has not been routine. Although two studies have demonstrated that changes in stimulation frequency (to higher frequency) and reductions in pulse width can have a short‐term positive impact on SNM outcome, to the present authors' knowledge no study has systematically explored a range of frequencies to determine whether an optimum exists.…”
Section: Introductionmentioning
confidence: 98%
“…35 the CCfis modestly improved (-2.4 to -2.7 points) during the 4-week RCt segments with high frequency or prolonged pulse width stimulation, but no other outcomes were significantly or meaningfully improved.…”
Section: Methodsmentioning
confidence: 73%
“…to assign a grade of low strength of evidence rather than insufficient, we required at least 2 moderate risk of bias studies or 1 sufficiently powered, low risk-of-bias RCt for a specific Sacral Nerve Stimulation five crossover RCts examined sns, mostly in 55-to 60-year-old women with mixed fi etiologies (table 1). the evidence for sns was insufficient because all 5 of the studies had moderate 27,36 or high 28,29,35 risk of bias, and none assessed the same treatment-outcome combination. Brief RCt summaries are below; details are provided in table 1 and appendix table 3. the RCts compared the sns versus supportive medical care on fi outcomes <1 year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although innumerable measures, scales and composite indices have been used, there is no acceptable gold standard or outcome measure. A selected list of recent RCTs spanning medical, biofeedback, injectable and surgical interventions are summarized in Table . This highlights the disparities in subject selection, trial design, outcome measures and risk of bias.…”
Section: Defining and Validating A Fi Endpointmentioning
confidence: 99%